2011
DOI: 10.1021/ma201486d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High Molecular Weight Poly[3-{tris(trimethylsiloxy)silyl}tricyclononenes-7] and Their Gas Permeation Properties

Abstract: |Macromolecules 2011, 44, 6637-6640 Macromolecules COMMUNICATION TO THE EDITOR type poly(III), and EA for compounds III, addition-type poly-(III), and MS for compound III. This material is available free of charge via the Internet at http://pubs.acs.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…Earlier we have described another metathesis polymer with three SiMe 3 groups per monomer unit where bulky SiMe 3 groups are linked via SiOSi bond to monomer units ( MPTCNSiO3 ) . So the comparison of the properties of these two polymers ( MPTCNSi3 and MPTCNSiO3 ) seemed interesting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier we have described another metathesis polymer with three SiMe 3 groups per monomer unit where bulky SiMe 3 groups are linked via SiOSi bond to monomer units ( MPTCNSiO3 ) . So the comparison of the properties of these two polymers ( MPTCNSi3 and MPTCNSiO3 ) seemed interesting.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that addition type polynorbornenes are more permeable than metathesis polymers but the latter are more readily obtained due to the high driving force of metathesis polymerization of high strain norbornene monomers . High gas permeability level of these polymers was caused by the presence of spherical bulky groups (e.g., trimethylsilyl groups or trimethylgermyl groups) and rigid polymer chains which disrupt a dense polymer chain package . Bulky SiMe 3 groups were also introduced into other classes of polymers (polyacetylenes, polystyrenes, polysulfones, poly(phenylene oxide), polyolefins).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in main chain flexibility or a substituent flexibility as a rule results in a decrease of gas permeability for light gases. The relationship between gas permeability of a polymer and its main chain flexibility can be illustrated for polymers of different classes: polyphenylacetylenes and polystyrenes, ROMP polynorbornenes and addition polynorbornenes . The influence of the flexibility of a substituent on gas permeability of polymers was demonstrated for polymers containing ‐SiMe 3 /SiMe 2 CH 2 SiMe 3 /SiMe 2 CH 2 CH 2 SiMe 3 and by the example of alkyl substituents in polyacetylenes and addition polynorbornenes .…”
Section: Resultsmentioning
confidence: 99%
“…Addition polynorbornenes are more permeable than their ROMP isomers . However, the metathesis polymers are more convenient objects for investigation of structure‐property correlations due to the very high driving force of metathesis polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained were used for the design and directed synthesis of highly gas permeable polymer materials from norbornenes. Thus, a new class of highly gas permeable polymers, namely, trimethylsilyl-substituted addition polynorbornenes was developed [7,[69][70]. These polymers belong to the group of the most permeable materials and exhibit solubility-controlled permeation of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%